2010
DOI: 10.3390/s101211189
|View full text |Cite
|
Sign up to set email alerts
|

Study on an Agricultural Environment Monitoring Server System using Wireless Sensor Networks

Abstract: This paper proposes an agricultural environment monitoring server system for monitoring information concerning an outdoors agricultural production environment utilizing Wireless Sensor Network (WSN) technology. The proposed agricultural environment monitoring server system collects environmental and soil information on the outdoors through WSN-based environmental and soil sensors, collects image information through CCTVs, and collects location information using GPS modules. This collected information is conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(63 citation statements)
references
References 10 publications
0
62
0
1
Order By: Relevance
“…The results showed that the WSN system can monitor the changes in temperature and humidity of honeybee colonies in real-time and indicate that temperature and humidity can, to a certain degree, be regarded as indicators of mite infection within honeybee colonies. Wireless communication and telemetric systems are feasible for online data collection tasks and animal monitoring in the field (Hwang et al, 2010), and greatly extend our ability to remotely monitor and control the physical environment. In addition, WSN is a wireless communication network that can self-organize and interact directly with the physical world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the WSN system can monitor the changes in temperature and humidity of honeybee colonies in real-time and indicate that temperature and humidity can, to a certain degree, be regarded as indicators of mite infection within honeybee colonies. Wireless communication and telemetric systems are feasible for online data collection tasks and animal monitoring in the field (Hwang et al, 2010), and greatly extend our ability to remotely monitor and control the physical environment. In addition, WSN is a wireless communication network that can self-organize and interact directly with the physical world.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, WSN is a wireless communication network that can self-organize and interact directly with the physical world. It can produce information that alerts to potential risks such as frost damage or toxic gases (Hwang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The hardware components that we used in this work make our proposed sensor nodes for agriculture cheaper than most of the WSN platforms on the market or than some studies have proposed, so far. Some studies use alternative platforms for the mainboard of the sensors node such as FS-ENGINE [9] and MCU MSP430 series [11][12]. The mainboard platforms in the previous studies are more expensive than the proposed ones.…”
Section: B System Architecturementioning
confidence: 99%
“…The MSP430F2274 microcontroller combines 16-MIPS performance with a 200-ksps 10-bit ADC and 2 op-amps, while the CC2500 multi-channel RF transceiver is designed for low-power wireless applications (Dixit, T. D 2013). The USB debugging interface enables eZ430-RF2500 to connect with a PC to send and receive data using the MSP430 application UART, which is recognized as the application backchannel (Hwang, J 2010).…”
Section: Design Of Microcontroller Modulementioning
confidence: 99%